2020
DOI: 10.1111/acel.13171
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulates the localization and degradation of p16INK4a

Abstract: The tumor suppressor protein p16 INK4a (p16) is a well‐established hallmark of aging that induces cellular senescence in response to stress. Previous studies have focused primarily on p16 regulation at the transcriptional level; comparatively little is known about the protein's intracellular localization and degradation. The autophagy–lysosomal pathway has been implicated in the subcellular trafficking and turnover of various stress‐response proteins and has also been shown to attenuate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Therefore, we designed another experiment, in which SAH rats treated with FoxO1 were intraperitoneally injected with RAP or CQ respectively. So far, most of the autophagy inducers discovered and widely used, such as RAP, a natural product, target the upstream of autophagy, which means that it can promote the occurrence of biological autophagosomes (Zhao H. et al., 2013 ), while CQ, as an autophagosome autophagy suppressor, can inhibit the occurrence of biological autophagosomes (Coryell et al., 2020 ). In our experiment, we found that both ad‐FoxO1 and RAP attenuated the injury of nerve function in rats during EBI after SAH, and this synergistic effect also further reduced cerebral edema and Evans blue extravasation, decreased hippocampus neuronal cell apoptosis, and declined inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we designed another experiment, in which SAH rats treated with FoxO1 were intraperitoneally injected with RAP or CQ respectively. So far, most of the autophagy inducers discovered and widely used, such as RAP, a natural product, target the upstream of autophagy, which means that it can promote the occurrence of biological autophagosomes (Zhao H. et al., 2013 ), while CQ, as an autophagosome autophagy suppressor, can inhibit the occurrence of biological autophagosomes (Coryell et al., 2020 ). In our experiment, we found that both ad‐FoxO1 and RAP attenuated the injury of nerve function in rats during EBI after SAH, and this synergistic effect also further reduced cerebral edema and Evans blue extravasation, decreased hippocampus neuronal cell apoptosis, and declined inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The knockout of autophagosome chaperone p62 attenuated p16 aggregates in lysosomes, indicating that p16 targets these vesicles through p62. As the regulator of autophagy, p16 performs a key role in the etiology of cancer and dementia (Coryell et al, 2020). Moreover, advanced age is a critical risk factor for most chronic diseases and functional defects in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This pro-autophagic effect of p16 INK4A was shown to be RB-dependent in glioblastoma [ 44 ] and could be partially explained by the transcriptional regulation of autophagic genes by the E2F transcription factors (see the subsection “”). More recently, some studies emphasized that the autophagic process regulates p16 INK4A quantity and localization, indicating crucial cross-talks and feedbacks between the cell-cycle regulators and autophagy [ 45 , 46 , 47 ]. Interestingly, the role of p16 INK4A in autophagy seems to be interrelated with its role during cellular senescence [ 48 ].…”
Section: Cell-cycle Regulators Modulate Autophagymentioning
confidence: 99%